COPA CASTELLINHO: THE THEMATIZATION OF SOCCERS IN A CRITICAL-DIALOGIC PERSPECTIVE - Santos, Mariana Gatto Lemos de Souza dos (2025)
The present study aims to socialize the experience of thematization of soccers within the scope of the critical-dialogical perspective of school Physical Education, admiring the students' pronunciations around the Copa Castellinho. The work flows in four stages. The first introduces the critical-dialogical perspective of Physical Education. The second focuses on soccers, listing possibilities for pedagogical treatment. Subsequently, the discussion of the experience report is presented as a methodological possibility, so that, finally, the experience of thematizing soccers in elementary school classes in a municipal school in São Gonçalo – Rio de Janeiro can be shared. In this way, the work outlines two points: the emergence of the understanding that the soccer’s world seems to be much broader than spectacular soccer; and the recognition of students as subjects who produce, create, transform and pronounce their own readings of soccers, based on the collective construction of the Copa Castellinho.